Longitudinal stability and cross-relations of prosocial behavior and the moral self-concept in early childhood - Sticker, Regina M.; Christner, Natalie; Gniewosz, Gabriela; Pletti, Carolina; Paulus, Markus (Cognitive development, 2023)
Children act prosocially very early in life by helping, comforting, or sharing with others. Recent research showed that preschool children differ in their representation of their other-oriented preferences (i.e., moral self-concept [MSC]). How stable are such behaviors and how stable is the MSC? And how does the MSC relate to prosocial behavior? In a longitudinal study, we investigated the stability and cross-relations between the MSC and prosocial behavior. We invited four- to six-year-old children to three measurement points (N = 127, 62 female). Children were mostly White and came from middle class families living in Germany. We assessed children’s helping, sharing, and comforting with established behavioral paradigms and the MSC with a puppet-interview. Results showed moderate stability of all behaviors and the MSC across the measurements, with strongest long-term stability for helping behavior and comforting MSC. Moreover, MSC at measurement two predicted prosocial behavior at measurement three even when taking earlier prosocial behavior into account. This effect was driven by the sharing dimension. Overall, the study points to stability of individual differences in the MSC and prosocial behaviors in early childhood. Moreover, it provides first empirical evidence for a developmental effect of the MSC on prosocial behavior. •Prosocial behaviors (sharing, helping, comforting) were stable in young children.•The moral self-concept showed stability in young children.•Moral self-concept predicted later prosocial behavior in a longitudinal study.